Satisfaction with Clinical Clerkship and Its Determinants Among Korean Medicine Students - Inseong Lee; Eui-Hyoung Hwang; Kang Kwon; Hye-Yoon Lee (Journal of Pharmacopuncture)
Objectives: Clinical clerkship is essential for medical education and provides students with hands-on experience and practical skills. Beyond monitoring, understanding the factors influencing satisfaction with clerkship can help improve educational quality. Methods: A satisfaction survey was administered to two cohorts of third- and fourth-year Korean medicine students who completed a 1-year clinical clerkship across 10 specialized departments. The survey consisted of nine items evaluated on a 5-point Likert scale. Descriptive statistics, multiple regression analysis and backward stepwise elimination were used to identify the key determinants of satisfaction with clinical clerkship. Results: "Opportunities for interaction with patients" received the lowest average score and showed the greatest variation. In contrast, "enthusiastic guidance from the faculty" had the most significant impact on satisfaction, with students reporting the highest average score. Sufficient opportunities for patient interaction and hands-on clinical skill practice also significantly influenced students' satisfaction, along with appropriate difficulty and time management. Conclusion: Improving student satisfaction with clinical clerkship requires enthusiastic guidance from the faculty, development of effective satisfaction survey tools, strengthening of outpatient department-based training, and efforts to diversify patient groups. Collaborative efforts across the Korean medicine community are essential to enhance the quality of clinical clerkship.